Growing up Masai - Shachtman, Tom, 1942-; Renn, Donn. (New York : Macmillan, 1981)
Describes the daily activities of two young members of the Masai tribe.
Keywords: Maasai (African people) -- Juvenile literature; Maasai (African people) -- Social life and customs